Spontaneous regression of advanced transverse colon cancer with remaining lymph node metastasis - Nishiura, Bunpei (Surg Case Rep, 2020)
BACKGROUND: The observation of spontaneous regression (SR) has been well documented for many cancer types, including renal cell carcinoma, non-Hodgkin’s lymphoma, leukemia, neuroblastoma, and malignant melanoma. However, the SR frequency in colorectal cancer is very rare. Therefore, the accumulation of SR colorectal cancer cases might contribute to find the regression mechanism. CASE PRESENTATION: A 67-year-old woman received colonoscopy due to being positive for fecal occult blood testing and was diagnosed as having a transverse colon cancer at a local hospital. She was admitted to our institution for surgical treatment of the colon cancer. The colonoscopy revealed a type 2 tumor of 13 mm in diameter at the hepatic flexure of the transverse colon. The enhanced computed tomography (CT) showed an enlarged lymph node in the intermediate lymph node region. The 18F-fluorodeoxyglucose positron emission tomography/CT showed no abnormal accumulation on the transverse colon; however, an abnormal accumulation was found at the enlarged lymph node. The patient was preoperatively diagnosed as having advanced transverse colon cancer with lymph node metastasis and underwent laparoscopic right hemicolectomy with D3 lymph node dissection. Pathological examination showed only a scar-like tissue and no cancerous lesion in the transverse colon, while a metastatic lymph node was histologically confirmed in the intermediate lymph node region. Loss of MLH1 and PMS2 expression was observed in the cancer cells of both biopsy specimens and resected lymph nodes. No recurrence was seen for 5 years after surgery. CONCLUSIONS: We reported a rare case of SR of the primary transverse colon cancer without regression of the metastatic regional lymph node. We considered that colorectal cancer with SR should be resected because even if SR of the primary lesion occurs, lymph node metastasis might have an inconsistent behavior as shown in the present case.